The Correlation between Adaptation to the Maternal Role and Social Support in a Sample of Iranian Primiparous Women - Khandan, Samineh; Riazi, Hedyeh; Amir Ali Akbari, Sedigheh; Nasiri, Malihe; Sheikhan, Zohreh (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Adaptation to the maternal role is an important factor for health of mothers and infants. With regards to numerous stresses after childbirth and effect of social support in modifying stresses, the present study was conducted for detecting the correlation between adaptation to the maternal role and social support in primiparous females. Methods: This cross-sectional study was performed on 260 primiparous females, who had referred to public health centers of Shahid Beheshti University of Medical Sciences in Tehran, during year 2016. Data gathering tools included the «Demographic Questionnaire», «Adaptation to the Maternal Role in Iranian Primiparous Women Questionnaire», «Multidimensional Scale of Perceived Social Support», and Edinburgh Postnatal Depression Scale. Data analysis was done using the SPSS software (version 22) and it was based on descriptive statistics and statistical independent t-test, Analysis of Variance (ANOVA), Spearman correlation, and linear regression. P value < 0.05 was considered significant. Results: The score of adaptation to a maternal role had a significant correlation with a total score of social support and its subscales (P = 0.001). Also, the adaptation to a maternal role had a reverse significant correlation with the mother and father’s education and the rate of family income, yet the results of the linear regression demonstrated that only two variables, “social support” and “mother’s education”, were significant in predicting the adaptation to a maternal role (P = 0.001), and they could predict 15% of variance for adapting to a maternal role. Conclusions: Social support is an effective factor for adaptation to the maternal role in primiparous females. Therefore, providing an appropriate situation for these supports is recommended. Also, it is required for health care providers to make sure about an adaptation to a maternal role, especially in mothers with higher education.